Psychiatric assessment in transplantation Avaliação psiquiátrica no transplante - Erick Messias; Christine E Skotzko (Universidade de São Paulo, 2000)
The implementation of the presumptive donor law in Brazil is expected to increase the availability of organs for transplantation. As medical management of end-stage organ dysfunction continues to improve, increasing numbers of potential transplant recipients will be available to meet this supply. There is mounting evidence that supports the involvement of skilled psychiatric practitioners in the selection of transplant candidates. Data supporting the influence of psychosocial factors on compliance and therefore medical outcomes continues to grow. The literature review allows delineating the components and rationale for comprehensive psychosocial evaluations as a component of preoperative transplantation evaluation. A implementação da figura do doador presumido e as recentes mudanças na regulamentação do transplante no Brasil irão aumentar a disponibilidade de órgãos no País. O avanço no cuidado de doentes portadores de insuficiência grave de órgãos, por sua vez, irá aumentar a demanda por esses mesmos órgãos. Há considerável literatura apoiando o envolvimento de psiquiatras no processo de seleção dos candidatos ao transplante. Pesquisas mostram que fatores psicossociais influenciam na adesão ao tratamento e, conseqüentemente, no prognóstico desses pacientes. A partir de uma revisão da literatura existente, articula-se os componentes e lógicas de uma avaliação psicossocial abrangente, propondo sua inserção na avaliação pré-operatória dos pacientes para o recebimento de órgão.